THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND DIET WITH THE INCIDENCE OF HYPERTENSION IN THE ELDERLY IN CEPOGO DISTRICT, BOYOLALI - Sukmaningsih, Wahyu Ratri; Aztiza, Zahra Anggra; Arisna, Arisna (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2023)
Hypertension is a disease characterized by blood pressure that is high above normal and persistent. This disease has become a health problem in Indonesia and in the world, so it is called the silent killer and often occurs with increasing age. The aim of this study was to determine the relationship between nutritional status and diet with the incidence of hypertension in the elderly in Cepogo Boyolali District. Observational analytical research with a cross sectional design, where the population in this study is the entire community in Cepogo District, with a sample size of 160 respondents who meet the inclusion criteria, the sampling technique is purposive sampling. Statistical tests used Chi-Square with research results showing that there was a relationship between nutritional status (p= 0.003) and diet (p= 0.000) with the incidence of hypertension in the elderly in Cepogo Boyolali District. Efforts should be made to increase motivation among the elderly regarding hypertension prevention and control programs. Keywords: Nutritional Status, Diet, Hypertension, Elderly